Analysis of the implementation of minimum service standards indicators radiology unit at RSUD X Padang - Rahmaddian, Tosi; Huvaid, Sevilla Ukhtil; Arikhman, Nova (Institute of Computer Science (IOCS), 2025)
Radiology services are an important and integrated part of healthcare services in hospitals. A survey on the Minimum Service Standards (SPM) for the radiology unit only evaluated 3 indicators, with problems found in the waiting time indicator that exceeded 3 hours. This study aims to evaluate the implementation of the SPM indicator in the radiology unit at RSUD X Padang. The research method used is qualitative, with data collection through in-depth interviews, FGDs, document review, and observations of 14 informants. The variables studied include the SPM indicators. The research results show the availability of SPM policies, but the number of radiology staff is not yet in accordance with the regulations. The survey was well-organized, but routine socialization has not been carried out. The service is not yet effective because the radiology specialist doctors are only present twice a week. Efforts to achieve the SPM targets are constrained by the limited presence of radiology specialist doctors. It can be concluded that the implementation of the SPM indicators in the radiology unit is not yet optimal. The suggestions given are the commitment of radiology specialist doctors to be present according to the set schedule, as well as proposing an increase in radiology staff.